Preserving stroke care during the COVID-19 pandemic: Potential issues and solutions. (21st July 2020) - Leira, Enrique C.; Russman, Andrew N.; Biller, José; Brown, Devin L.; Bushnell, Cheryl D.; Caso, Valeria; Chamorro, Angel; Creutzfeldt, Claire J.; Cruz-Flores, Salvador; Elkind, Mitchell S.V.; Fayad, Pierre; Froehler, Michael T.; et al.
Abstract : The coronavirus 2019 (COVID-19) pandemic requires drastic changes in allocation of resources, which can affect the delivery of stroke care, and many providers are seeking guidance. As caregivers, we are guided by 3 distinct principles that will occasionally conflict during the pandemic: (1) we must ensure the best care for those stricken with COVID-19, (2) we must provide excellent care and advocacy for patients with cerebrovascular disease and their families, and (3) we must advocate for the safety of health care personnel managing patients with stroke, with particular attention to those most vulnerable, including trainees. This descriptive review by a diverse group of experts in stroke care aims to provide advice by specifically addressing the potential impact of this pandemic on (1) the quality of the stroke care delivered, (2) ethical considerations in stroke care, (3) safety and logistic issues for providers of patients with stroke, and (4) stroke research. Our recommendations on these issues represent our best opinions given the available information, but are subject to revision as the situation related to the COVID-19 pandemic continues to evolve. We expect that ongoing emergent research will offer additional insights that will provide evidence that could prompt the modification or removal of some of these recommendations.